LEADERSHIP POLICY IN DEVELOPING OF ISLAMIC SCHOOL EDUCATION CURRICULUM AT DARULARAFAH BOARDING SCHOOL IN DELI SERDANG REGENCY - Muhammad Hamzah; Syafaruddin Syafaruddin; Syaiful Akhyar (UIN Sumatera Utara Medan, 2019)
This study aimed to determine the process of formulating policies, implementing policies, performance, stakeholders support, and the policies of the boarding chairman in developing the Islamic school curriculum at the Darularafah Boarding School boarding school in Deli Serdang Regency. The data were obtained through interviews, observation, and documentation. The data analysis was done through data reduction, data presentation, and data verification. The results of this study were 1) The formulation of boarding school leaders' policies was carried out through annual meetings and deliberations attended by chairman, chiefs of fields, principals, teachers and communities to formulate five work programs related to the system of movement, organization and leadership, network, resources, and actions of service, 2) Implementation of formulation of the curriculumdevelopment program implemented at the Darularafah boarding school was carried out at the end of each year, then socialized to and through the prepared fields. 3) the performance of the implementation of the boarding schoolleadershippolicy was suited to its development as well as the boarding school's  needs, 4) Stakeholder supported in implementing the policies of the boarding school leadership that was very supportive in the internal environment, as well as from the external / community